ANALISIS BUTIR SOAL UJIAN - Dewi Rahmayati; Nani Suwarni; Dedy Miswar (JPG (Jurnal Penelitian Geografi), 2013)
The aim to of this research was to analyze the odd semester exam questions in Geography subject to the first grade students at SMA Bina Mulya Bandar Lampung in the year of 2011/2012 which include the validity, reliability, power of difficulty, discrimination power, and answer patterns.This method used in the research was descriptive method. The results of the analysis showed that the quality which was seen from the 1) Validity there were 11 or 22% of questions which were valid and the rest there were 39 questions or 78% of questions were invalid. 2) From the level of difficulty, there were 26 questions or 52% of questions which had average level of difficulty, it meant that they could be used in exam, and there were 24 or 48% of questions which had difficult and easy level. 3) From the discrimination power, there were 12 questions or 24% questions which had good discrimination power and there were 38 or 76% questions which had low and negative. 4) From the answer patterns, it is known that in general all destructor in the questions were function properly. Key Word: analyze exam question